Barrier film, laminate based thereon, and packaging product

By incorporating a coating layer and avoiding direct contact with guide rolls, the barrier film significantly reduces pinholes, enhancing oxygen and water vapor barrier properties, achieving superior performance in barrier films.

JP2025011757APending Publication Date: 2025-01-24DAI NIPPON PRINTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023114059
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Conventional barrier films with aluminum vapor-deposited films suffer from unavoidable pinholes, leading to deterioration of oxygen and water vapor barrier properties, which cannot be effectively mitigated by increasing film thickness alone.

Method used

A barrier film structure is designed with a resin base material and an aluminum vapor-deposited film, where a coating layer is introduced between or on the aluminum vapor-deposited film, and the film is processed to avoid direct contact with guide rolls during deposition, reducing pinhole occurrence to 0.100% or less.

Benefits of technology

The film achieves excellent oxygen and water vapor barrier properties with reduced pinholes, maintaining high performance even after processing, with oxygen permeability of 0.30 cc/m²·day·atm or less and water vapor permeability of 0.30 g/m²·day or less at specified conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011757000001_ABST
    Figure 2025011757000001_ABST
Patent Text Reader

Abstract

To provide a barrier film with excellent oxygen- and water vapor-barrier properties by reducing pinhole formation originating in an aluminum-metallized film.SOLUTION: A barrier film comprises a resin substrate, an aluminum-metallized film and an optional coating layer that are laminated in this order, where the pinhole incidence is 0.100% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a barrier film, and a laminate and a packaging product using the same. [Background technology]

[0002] Conventionally, barrier films having a metal aluminum vapor-deposited film (hereinafter simply referred to as aluminum vapor-deposited film) formed on a substrate such as a long film or sheet of plastic have been used in various applications such as packaging products. This barrier film has a barrier function against oxygen and water vapor.

[0003] In general, a barrier film having an aluminum metal vapor deposition film is produced by heating an aluminum metal evaporation source on a substrate to evaporate the aluminum metal to form a thin aluminum metal film on the substrate.

[0004] For example, Patent Document 1 listed below discloses a barrier film including a base film, a vapor-deposited layer whose composition changes continuously from an aluminum vapor-deposited layer to an aluminum oxide vapor-deposited layer, and a gas barrier resin layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication WO2018 / 147137 Summary of the Invention [Problem to be solved by the invention]

[0006] In conventional barrier films having an aluminum vapor-deposited film, the occurrence of pinholes in the aluminum vapor-deposited film is unavoidable, which causes a problem of reduced barrier properties. According to the findings of the present inventors, the reduction in barrier properties due to the occurrence of pinholes occurs to a certain degree even if the vapor-deposited film thickness is increased, and the reduction in barrier properties cannot be eliminated by controlling the film thickness alone.

[0007] An object of the present invention is to provide a barrier film that is excellent in oxygen barrier property and water vapor barrier property by reducing the occurrence of pinholes originating from an aluminum vapor deposition film. [Means for solving the problem]

[0008] The inventors conducted extensive research to solve the above-mentioned problems and found that, in the structure of conventional vapor deposition devices, when an aluminum-vapor-deposited film immediately after deposition is taken up through a number of rolls such as guide rolls, the aluminum-vapor-deposited surface comes into direct contact with the roll surfaces, causing pinholes to form and reducing the barrier properties. This led to the completion of the present invention.

[0009] Specifically, the present invention provides the following:

[0010] (1) A barrier film comprising a resin substrate and an aluminum vapor deposition film laminated in this order, The barrier film has a pinhole incidence rate, as defined below, of 0.100% or less. <Definition of Pinhole Incidence Rate> One side of the barrier film is irradiated with a halogen light source at an illuminance of 5500±550 lux, and an arbitrary 2.8 mm × 2.1 mm area is enlarged from the other side of the barrier film using an optical microscope, and a 1280 × 964 pixel image of the enlarged image is taken. Using image analysis software, the taken image is converted into a monochrome image with 256 gradations. The value obtained by adding 30 gradations to the most frequent luminance value in the monochrome image is set as a threshold, and the luminance is binarized by setting values ​​below the threshold as black pixels and values ​​above the threshold as white pixels, and is calculated using the following formula. Pinhole occurrence rate (%) = 100 x (white pixels / total pixels)

[0011] (2) The barrier film according to (1), wherein a coating layer is disposed between the resin substrate and the aluminum vapor-deposited film or on the aluminum vapor-deposited film.

[0012] (3) The barrier film according to (1) or (2), wherein the coating layer is a cured product of a resin composition containing an alkoxysilane and a hydroxyl group-containing water-soluble resin.

[0013] (4) The barrier film according to (1) or (2) has an oxygen permeability of 0.3 cc / m at 23°C and 90% RH as measured in accordance with JIS K 7126-2. 2 Barrier film that is less than 1000m² / day atm.

[0014] (5) The barrier film according to (1) or (2) has a water vapor transmission rate of 0.3 g / m at 40°C and 100% RH as measured according to JIS K 7129 B method. 2 · Day or less, barrier film.

[0015] (6) A laminate comprising the barrier film according to (1) or (2) and a sealant layer.

[0016] (7) A packaging product comprising the laminate described in (6). Effect of the Invention

[0017] The barrier film of the present invention has excellent oxygen barrier properties and water vapor barrier properties by reducing the occurrence of pinholes originating from the aluminum vapor deposition film. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a barrier film according to the present embodiment, in which FIG. 1(A) is a schematic diagram showing the layer structure of a first embodiment, FIG. 1(B) is a schematic diagram showing the layer structure of a second embodiment, and FIG. 1(C) is a schematic diagram showing the layer structure of a third embodiment. [Diagram 2] FIG. 11 is a diagram showing an example of a luminance histogram according to the second embodiment. [Diagram 3] FIG. 3 is a diagram showing the luminance histogram of FIG. 2 converted into a binary value. [Figure 4] FIG. 13 is a diagram showing an example of a luminance histogram in Comparative Example 3. [Diagram 5] FIG. 5 is a diagram showing a binarized version of the luminance histogram in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as appropriate within the scope of the object of the present invention. In addition, in this specification, the expression "X to Y" (X and Y are arbitrary numbers) means "X or more and Y or less."

[0020] In this specification, "laminated in this order" means that the substrate, the vapor-deposited film, and the coating layer are laminated in this order, and other layers, such as an anchor coat layer or a primer layer, may be laminated between these layers.

[0021] 1(A) to (C) are cross-sectional views showing an example of a barrier film according to the present embodiment. The barrier film in FIG. 1(A) to (C) includes a substrate 1, an aluminum vapor deposition film 2, and a coating layer 3 that is provided as needed.

[0022] First Embodiment 1(A) is an example in which a substrate 1 and an aluminum vapor-deposited film 2 are laminated together. The aluminum vapor-deposited film 2 is located on one surface of the substrate 1.

[0023] Each layer constituting the barrier film will be described below.

[0024] [Base material] The substrate 1 is a layer made of a resin. The resin is not particularly limited, and a known resin film or sheet can be used. Specifically, the substrate may be a polyester substrate or a polyolefin substrate. As the polyester substrate, for example, a polyester resin including a polyethylene terephthalate resin, a polybutylene terephthalate resin, a polyethylene naphthalate resin, or the like can be used. As the polyolefin substrate, for example, a polypropylene resin can be used.

[0025] Among polyester resins, it is preferable to use polyethylene terephthalate resins or polybutylene terephthalate resins. The polyester film used as the substrate 1 may be stretched in a predetermined direction. In this case, the polyester film may be a uniaxially stretched film stretched in one predetermined direction, or a biaxially stretched film stretched in two predetermined directions. For example, when a film made of polyethylene terephthalate is used as the substrate 1, a biaxially stretched polyethylene terephthalate film can be used.

[0026] When a film made of polypropylene resin is used as the substrate 1, a biaxially oriented polypropylene film can be used.

[0027] In the case of a polyester film, the film thickness is not particularly limited, but from the viewpoint of flexibility and shape retention, it is preferably in the range of 5 μm to 100 μm, more preferably 10 μm to 50 μm. If the thickness of the polyester film is within the above range, it is easy to bend and does not break during transportation, and is easy to handle in a film forming device used for manufacturing a barrier film having an aluminum vapor deposition film 2.

[0028] In the case of a polyolefin film, the film thickness is preferably in the range of 10 μm or more and 100 μm or less, more preferably in the range of 15 μm or more and 50 μm or less, from the viewpoints of flexibility and shape retention.

[0029] As the polyethylene terephthalate film (PET film), in addition to conventionally known PET films, biomass PET film, recycled PET film, and high stiffness PET film (tough PET film) may be used as the substrate 1. It may have a single layer or a multi-layer structure of two or more layers, and in the case of a multi-layer structure, the layers may have the same composition or different compositions. In the case of a multi-layer structure, each layer may be bonded with an adhesive layer or the like.

[0030] The biopolyester that makes up the biomass PET film is composed of diol units and dicarboxylic acid units, and is obtained by a polycondensation reaction using ethylene glycol derived from biomass as the diol units and dicarboxylic acid derived from fossil fuels as the dicarboxylic acid units.

[0031] Biomass-derived ethylene glycol is made from ethanol (biomass ethanol) produced from biomass as a raw material. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. Commercially available biomass ethylene glycol may also be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.

[0032] The dicarboxylic acid unit of the polyester uses a dicarboxylic acid derived from a fossil fuel. As the dicarboxylic acid, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and derivatives thereof can be used without limitation. As the aromatic dicarboxylic acid, terephthalic acid and isophthalic acid can be mentioned, and as the derivative of the aromatic dicarboxylic acid, lower alkyl ester of aromatic dicarboxylic acid, specifically, methyl ester, ethyl ester, propyl ester, butyl ester, etc. can be mentioned. Among these, terephthalic acid is preferable, and as the derivative of the aromatic dicarboxylic acid, dimethyl terephthalate is preferable.

[0033] In addition, specific examples of the aliphatic dicarboxylic acid include linear or alicyclic dicarboxylic acids having 2 to 40 carbon atoms, such as oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, dimer acid, and cyclohexanedicarboxylic acid. In addition, examples of the derivatives of the aliphatic dicarboxylic acids include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the above aliphatic dicarboxylic acids, and cyclic acid anhydrides of the above aliphatic dicarboxylic acids, such as succinic anhydride. Among these, adipic acid, succinic acid, dimer acid, or a mixture thereof is preferred, and those containing succinic acid as the main component are particularly preferred. Examples of the derivatives of the aliphatic dicarboxylic acid include methyl esters of adipic acid and succinic acid, or a mixture thereof. These dicarboxylic acids can be used alone or in combination of two or more.

[0034] The biopolyester may be a copolymer polyester in which a copolymer component is added as a third component in addition to the above diol component and dicarboxylic acid component. Specific examples of the copolymer component include bifunctional oxycarboxylic acid, and at least one polyfunctional compound selected from the group consisting of trifunctional or more polyhydric alcohols, trifunctional or more polycarboxylic acids and / or their anhydrides, and trifunctional or more oxycarboxylic acids to form a crosslinked structure. Among these copolymer components, bifunctional and / or trifunctional or more oxycarboxylic acids are particularly preferably used because they tend to easily produce copolymer polyesters with a high degree of polymerization. Among them, the use of trifunctional or more oxycarboxylic acids is most preferred because a polyester with a high degree of polymerization can be easily produced with a very small amount without using a chain extender described later.

[0035] The biopolyester may be a high molecular weight polyester obtained by chain-extending (coupling) these copolymer polyesters. As the chain extender, a carbonate compound, a diisocyanate compound, or the like may be used, and the amount of carbonate bond and urethane bond is usually 10 mol % or less, preferably 5 mol % or less, more preferably 3 mol % or less, based on 100 mol % of all monomer units constituting the polyester.

[0036] Specific examples of carbonate compounds include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, ethylene carbonate, diamyl carbonate, dicyclohexyl carbonate, etc. In addition, carbonate compounds composed of the same or different hydroxy compounds derived from hydroxy compounds such as phenols and alcohols can be used.

[0037] Specific examples of the diisocyanate compound include known diisocyanates such as 2,4-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, diphenylmethane diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.

[0038] The biopolyester can be obtained by a conventionally known method of polycondensing the above-mentioned diol unit and dicarboxylic acid unit. Specifically, the biopolyester can be produced by a general melt polymerization method in which an esterification reaction and / or an ester exchange reaction between the above-mentioned dicarboxylic acid component and the diol component is followed by a polycondensation reaction under reduced pressure, or by a known solution heating dehydration condensation method using an organic solvent.

[0039] The amount of diol used in producing the biopolyester is substantially equimolar to 100 moles of the dicarboxylic acid or its derivative, but is generally used in an excess of 0.1 to 20 mol % because distillates are generated during the esterification and / or transesterification reaction and / or condensation polymerization reaction.

[0040] The polycondensation reaction is preferably carried out in the presence of a polymerization catalyst. The timing of adding the polymerization catalyst is not particularly limited as long as it is before the polycondensation reaction, and the catalyst may be added when the raw materials are charged or when the pressure reduction is started.

[0041] The polymerization catalyst generally includes compounds containing metal elements of Groups 1 to 14 of the periodic table, excluding hydrogen and carbon. Specifically, compounds containing organic groups such as carboxylates, alkoxy salts, organic sulfonates, or β-diketonate salts containing at least one metal selected from the group consisting of titanium, zirconium, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium, and potassium, and further inorganic compounds such as oxides and halides of the above metals and mixtures thereof. Among these, metal compounds containing titanium, zirconium, germanium, zinc, aluminum, magnesium, and calcium, and mixtures thereof are preferred, and titanium compounds, zirconium compounds, and germanium compounds are particularly preferred. In addition, the catalyst is preferably a compound that is liquid during polymerization or dissolves in an ester oligomer or polyester, because the polymerization rate increases when the catalyst is in a molten or dissolved state during polymerization.

[0042] As the titanium compound, tetraalkyl titanate is preferred, specifically, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof can be mentioned. In addition, titanium (oxy) acetylacetonate, titanium tetraacetylacetonate, titanium (diisopropoxide) acetylacetonate, titanium bis (ammonium lactate) dihydroxide, titanium bis (ethylacetoacetate) diisopropoxide, titanium (triethanolamine) isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolamine, butyl titanate dimer, etc. can also be preferably used. Furthermore, titanium oxide and composite oxides containing titanium and silicon can also be preferably used. Among these, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxytitanium stearate, titanium lactate, butyl titanate dimer, titanium oxide, and titania / silica composite oxide (e.g., product name: C-94 manufactured by Acordis Industrial Fibers) are preferred, and tetra-n-butyl titanate, polyhydroxytitanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and titania / silica composite oxide (e.g., product name: C-94 manufactured by Acordis Industrial Fibers) are particularly preferred.

[0043] Specific examples of zirconium compounds include zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof. Zirconium oxide is also useful. Alternatively, for example, a composite oxide containing zirconium and silicon may be used. Among these, zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, ammonium zirconium oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide are preferred.

[0044] Specific examples of germanium compounds include inorganic germanium compounds such as germanium oxide and germanium chloride, and organic germanium compounds such as tetraalkoxygermanium. In view of cost and availability, germanium oxide, tetraethoxygermanium, and tetrabutoxygermanium are preferred, with germanium oxide being particularly preferred.

[0045] When using metal compounds as these polymerization catalysts, the amount of catalyst used is usually 5 ppm or more, preferably 10 ppm or more, and the upper limit is usually 30,000 ppm or less, preferably 1,000 ppm or less, more preferably 250 ppm or less, and particularly preferably 130 ppm or less, as the amount of metal relative to the polyester produced. If the amount of catalyst used is too large, not only is it economically disadvantageous, but the thermal stability of the polymer is also reduced, whereas if the amount is too small, the polymerization activity is reduced, and the decomposition of the polymer is easily induced during the polymer production. As for the amount of catalyst used here, the method of reducing the amount of catalyst used is a preferred embodiment, since the amount of terminal carboxyl groups of the polyester produced is reduced as the amount of catalyst used is reduced.

[0046] The reaction temperature of the esterification reaction and / or transesterification reaction between the dicarboxylic acid component and the diol component is usually in the range of 150 to 260° C., and the reaction atmosphere is usually an inert gas atmosphere such as nitrogen or argon, etc. The reaction pressure is usually normal pressure to 10 kPa, and the reaction time is usually about 1 hour to 10 hours.

[0047] In the above-mentioned production process, a chain extender (coupling agent) may be added to the reaction system. The chain extender is added to the reaction system in a homogeneous molten state without a solvent after the completion of polycondensation, and reacted with the polyester obtained by polycondensation.

[0048] The high molecular weight polyester using these chain extenders (coupling agents) can be produced by using known techniques. After the polycondensation is completed, the chain extender is added to the reaction system in a homogeneous molten state without a solvent, and reacted with the polyester obtained by the polycondensation. Specifically, a polyester resin with a higher molecular weight can be obtained by reacting the chain extender with a polyester prepolymer obtained by catalytic reaction of a diol with a dicarboxylic acid, which has a terminal group substantially having a hydroxyl group and has a mass average molecular weight (Mw) of 20,000 or more, preferably 40,000 or more. If the prepolymer has a mass average molecular weight of 20,000 or more, a small amount of coupling agent is used, and since it is not affected by the remaining catalyst even under harsh conditions such as a molten state, a high molecular weight polyester can be produced without generating gel during the reaction.

[0049] The obtained biopolyester may be solidified and then subjected to solid-phase polymerization as necessary to further increase the degree of polymerization or to remove oligomers such as cyclic trimers. Specifically, the polyester is chipped and dried, then heated at a temperature of 100 to 180°C for about 1 to 8 hours to pre-crystallize the polyester, and then heated at a temperature of 190 to 230°C under an inert gas flow or under reduced pressure for 1 to several tens of hours.

[0050] The intrinsic viscosity of the biopolyester obtained as described above (measured in an orthochlorophenol solution at 35°C) is preferably 0.5 dl / g to 1.5 dl / g, more preferably 0.6 dl / g to 1.2 dl / g. If the intrinsic viscosity is less than 0.5 dl / g, the mechanical properties required for the polyester film as a semi-transmissive reflective film substrate, including tear strength, may be insufficient. On the other hand, if the intrinsic viscosity exceeds 1.5 dl / g, productivity is impaired in the raw material production process and film formation process.

[0051] In the biopolyester production process or to the produced biopolyester resin, various additives may be added within the range that does not impair its properties, such as plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, thread friction reducers, release agents, antioxidants, ion exchange agents, color pigments, etc. These additives are added in the range of 5 to 50% by mass, preferably 5 to 20% by mass, based on the total biopolyester resin composition.

[0052] The recycled polyester that makes up the recycled PET film is a polyester obtained by recycling a product made of a polyester resin that is composed of diol units and dicarboxylic acid units and is obtained by a polycondensation reaction using a diol derived from a fossil fuel or ethylene glycol derived from biomass as the diol unit and a dicarboxylic acid derived from a fossil fuel as the dicarboxylic acid unit.

[0053] The resin that is the basis of the recycled polyester (that is, the polyester resin before recycling) may be one in which both the diol unit and the dicarboxylic acid unit are made from raw materials derived from fossil fuels, or may be the biomass polyester described above.

[0054] Examples of the diol derived from fossil fuels used in the resin that is the basis of the recycled polyester include aliphatic diols, aromatic diols, and derivatives thereof, and those used as diol units in conventional polyesters can be suitably used. The aliphatic diol is not particularly limited as long as it is an aliphatic or alicyclic compound having two OH groups, but examples of the aliphatic diol include aliphatic diols having a carbon number of 2 or more and usually 10 or less, preferably 6 or less. Specific examples include ethylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, decamethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol. These may be used alone or in a mixture of two or more. Among these, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, and 1,4-cyclohexanedimethanol are preferred, and ethylene glycol is particularly preferred.

[0055] The resin composition containing biopolyester preferably contains 10 to 19% of biomass-derived carbon based on radiocarbon (C14) measurement relative to the total carbon in the polyester. Carbon dioxide in the atmosphere contains a certain proportion of C14 (105.5 pMC), and it is known that the C14 content in plants that grow by absorbing carbon dioxide in the atmosphere, such as corn, is also about 105.5 pMC. It is also known that fossil fuels contain almost no C14. Therefore, the proportion of biomass-derived carbon can be calculated by measuring the proportion of C14 in the total carbon atoms in the polyester. In the present invention, the content of biomass-derived carbon, Pbio, when the content of C14 in the polyester is PC14, is defined as follows. Pbio(%)=PC14 / 105.5×100

[0056] Taking polyethylene terephthalate as an example, polyethylene terephthalate is a polymer of ethylene glycol containing 2 carbon atoms and terephthalic acid containing 8 carbon atoms at a molar ratio of 1:1. Therefore, when only biomass-derived ethylene glycol is used, the content of biomass-derived carbon in the polyester, Pbio, is 20%. In the present invention, the content of biomass-derived carbon measured by radiocarbon (C14) is preferably 10 to 19% relative to the total carbon in the resin composition. If the biomass-derived carbon content in the resin composition is less than 10%, the effect as a carbon offset material is poor. On the other hand, as described above, the biomass-derived carbon content in the resin composition is preferably as close to 20% as possible, but from the viewpoint of problems in the film manufacturing process and physical properties, it is preferable that the resin contains recycled polyester and additives as described above, so the actual upper limit is 18%.

[0057] An anchor coat layer (AC layer, also called a primer layer) may be formed on the surface of the substrate 1. Examples of the anchor coat layer include polyurethane resin, polyamide resin, epoxy resin, phenol resin, (meth)acrylic resin, and polyvinyl acetate resin. Examples of the polyurethane resin include acrylic urethane resin and polyester urethane resin.

[0058] The substrate 1 is preferably transparent. Specifically, it is preferable that the total light transmittance measured based on JIS K 7361-1:1997 is high. Specifically, the total light transmittance of the substrate 1 is preferably 85% or more, and more preferably 90% or more.

[0059] [Aluminum vapor deposition film] Next, the aluminum vapor deposition film 2 will be described. The aluminum vapor deposition film 2 is a vapor deposition film of metallic aluminum formed by physical vapor deposition (PVD). By forming the aluminum vapor deposition film, it is possible to improve the light blocking property while improving the gas barrier property.

[0060] Examples of physical vapor deposition (PVD) methods include vacuum deposition, sputtering, ion plating, and ion cluster beam methods. Specifically, a deposition film can be formed using a vacuum deposition method in which aluminum is used as a raw material, heated to vaporize it, and then deposited on one side of a resin substrate (resin film). The deposition material can be heated by, for example, a resistance heating method, a high-frequency induction heating method, or an electron beam heating method (EB).

[0061] The thickness of the aluminum vapor deposition film is preferably 20 nm or more and 500 nm or less, more preferably 30 nm or more and 500 nm or less, and more preferably 40 nm or more and 500 nm or less. If the thickness of the aluminum vapor deposition film is within the above range, sufficient light blocking properties can be obtained.

[0062] The thickness of the aluminum vapor deposition film formed on the substrate can also be understood as the optical density (OD value) of the substrate and the aluminum vapor deposition film. The OD value is preferably 1.0 or more and 32.0 or less, and the lower limit is more preferably 1.7 or more, and even more preferably 2.3 or more. If the thickness of the aluminum vapor deposition film is within the above range, sufficient light blocking properties can be obtained.

[0063] As described later, in order to obtain sufficient gas barrier properties, it is not enough to simply increase the thickness of the aluminum vapor deposition film, and it is necessary to reduce the pinhole occurrence rate, which will be described later. According to the present invention, even if the film has a thin film thickness with an OD value of 2.0 or more and 3.0 or less, it is possible to provide high barrier properties by suppressing the pinhole occurrence rate, which will be described later.

[0064] <Second embodiment> The second embodiment shown in Fig. 1(B) is an example in which a substrate 1, an aluminum vapor-deposited film 2, and a coating layer 3 are laminated in this order. The coating layer 3 is located on the surface of the barrier film, and is different from the first embodiment in that a coating layer 3 is provided. The explanation of the substrate 1 and the aluminum vapor-deposited film 2 is the same as in the first embodiment. The coating layer 3 will be explained below.

[0065] (covering layer) The coating layer 3 laminated on the surface of the aluminum vapor-deposited film 2 is an organic coating film that protects the aluminum vapor-deposited film 2 mechanically and chemically and also improves the barrier performance of the laminated film having barrier properties.

[0066] The coating layer 3 is formed by applying and solidifying a barrier coating agent onto the aluminum vapor deposition film. The barrier coating agent is composed of a metal alkoxide, a water-soluble polymer, a silane coupling agent (which is added as needed), a sol-gel catalyst, an acid, and the like.

[0067] As the metal alkoxide, the general formula R1 n M(OR 2 ) m (wherein, in the formula, R1 and R2 represent an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M), and examples of the metal atom represented by M of the metal alkoxide include silicon, zirconium, titanium, aluminum, and the like. For example, it is preferable to use an alkoxysilane in which M is Si.

[0068] The above alkoxysilane is, for example, one represented by the general formula Si(ORa)4 (wherein Ra represents a lower alkyl group). In the above, Ra may be a methyl group, an ethyl group, an n-propyl group, an n-butyl group, or the like. Specific examples of the above alkoxysilane include tetramethoxysilane Si(OCH3)4, tetraethoxysilane Si(OC2H5)4, tetrapropoxysilane Si(OC3H7)4, tetrabutoxysilane Si(OC4H9)4, and the like. The above alkoxides may be used in combination of two or more kinds.

[0069] Silane coupling agents having reactive groups such as vinyl, epoxy, methacryl, and amino groups can be used. In particular, organoalkoxysilanes having epoxy groups are suitable, and for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropyldimethylmethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyldimethylethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be used. The above-mentioned silane coupling agents may be used alone or in combination of two or more.

[0070] In particular, the crosslink density of the cured film of the coating layer using bifunctional compounds such as γ-glycidoxypropylmethyldimethoxysilane and γ-glycidoxypropylmethyldiethoxysilane is lower than that of a system using trialkoxysilane. Therefore, the cured film has excellent gas barrier properties and hot water treatment resistance, while also being flexible and has excellent bending resistance, so that the gas barrier properties of the packaging material using the barrier film are unlikely to deteriorate even after the Gelbo flex test.

[0071] The water-soluble polymer may be a polyvinyl alcohol resin or an ethylene-vinyl alcohol copolymer, or may be a combination of a polyvinyl alcohol resin and an ethylene-vinyl alcohol copolymer. In the coating layer 3 according to the present embodiment, a polyvinyl alcohol resin is preferred.

[0072] Generally, the polyvinyl alcohol resin can be one obtained by saponifying polyvinyl acetate. The polyvinyl alcohol resin can be a partially saponified polyvinyl alcohol resin in which several tens of percent of acetate groups remain, a completely saponified polyvinyl alcohol in which no acetate groups remain, or a modified polyvinyl alcohol resin in which OH groups have been modified. As the polyvinyl alcohol resin, it is necessary to use at least one that undergoes crystallization to improve the film hardness of the gas barrier coating film, and preferably has a saponification degree of 70% or more. In addition, any polyvinyl alcohol resin can be used as long as it has a polymerization degree within the range used in the conventional sol-gel method (about 100 to 5000). Examples of such polyvinyl alcohol resins include RS resin "RS-110 (saponification degree = 99%, polymerization degree = 1,000)" manufactured by Kuraray Co., Ltd. and "GOHSENOL NM-14 (saponification degree = 99%, polymerization degree = 1,400)" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.

[0073] The ethylene-vinyl alcohol copolymer may be a saponified copolymer of ethylene and vinyl acetate, i.e., a product obtained by saponifying an ethylene-vinyl acetate random copolymer. For example, it may be a partially saponified product in which several tens of mol% of acetate groups remain, or a completely saponified product in which only a few mol% of acetate groups remain or no acetate groups remain, and is not particularly limited. However, from the viewpoint of barrier properties, the lower limit of the saponification degree is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more. The upper limit is 100% or less.

[0074] As the sol-gel catalyst, an acid or amine compound is preferable.

[0075] As the acid, for example, mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as acetic acid, tartaric acid, etc. can be used.

[0076] The content of the acid is preferably 0.001 to 0.05 mol%, more preferably 0.01 to 0.03 mol%, based on the total molar amount of alkoxy groups in the metal alkoxide. If the content is less than 0.001%, the catalytic effect is too small, whereas if the content is more than 0.05 mol%, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0077] As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable. Specifically, for example, N,N-dimethylbenzylamine, tripropylamine, tributylamine, tripentylamine, etc. can be used. In particular, N,N-dimethylbenzylamine is preferable.

[0078] The content of the amine compound is preferably, for example, 0.01 to 1.0 part by mass, particularly 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. If the content is less than 0.01 part by mass, the catalytic effect is too small, whereas if the content is more than 1.0 part by mass, the catalytic effect is too strong, causing the reaction rate to become too fast and tending to become non-uniform.

[0079] As the solvent, it is preferable to use water or alcohol such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropanol, or n-butanol.

[0080] The barrier coating layer 3 formed as described above has a layer thickness of 100 to 500 nm, preferably 200 to 400 nm. This range is preferable because the coating film does not crack and sufficiently covers the surface of the deposited film.

[0081] When the barrier coating agent contains a silane coupling agent, 5 to 10 parts by mass of a water-soluble polymer such as a polyvinyl alcohol resin and 1 to 10 parts by mass of the silane coupling agent can be used per 100 parts by mass of alkoxysilane. This allows the flexibility of the film to be maintained. In the above, if the silane coupling agent is used in an amount exceeding 20 parts by mass, the rigidity and brittleness of the barrier coating film formed increases, which is not preferable.

[0082] Furthermore, when a silane coupling agent is not contained, the ratio of metal alkoxide can be reduced and the barrier properties can be improved by using 10 to 20 parts by mass of a water-soluble polymer such as a polyvinyl alcohol resin per 100 parts by mass of alkoxysilane.

[0083] The lower limit of the IO value (the solid content ratio of metal alkoxide such as tetraethoxysilane to water-soluble resin such as polyvinyl alcohol) in the coating layer is preferably 1.5 or more, more preferably 1.9 or more. The upper limit is preferably 4.0 or less, more preferably 3.5 or less. If it exceeds 4.0, the barrier property may decrease after the post-process or Gelbo flex test, which is not preferable, and if it is less than 1.5, the barrier property after retort treatment is decreased, which is not preferable.

[0084] The coating layer 3 may be formed by applying and solidifying a resin composition containing one or more resins selected from a urethane resin, an acrylic resin, a polyvinylidene chloride resin, and a polyvinyl alcohol resin, in addition to the above-mentioned metal alkoxide and water-soluble polymer. If necessary, the coating layer 3 may further contain a silane coupling agent or silica fine particles.

[0085] By including a urethane resin in the coating layer 3, the coating layer 3 has appropriate elasticity or flexibility, and the influence of pressure on the deposition film during printing or lamination can be reduced, and deterioration of the gas barrier property can be suppressed. As the urethane resin, any of the conventionally known polyester urethane resins and polyether urethane resins can be used. As such a urethane resin, a reaction product of a polyol, such as a polyester polyol or a polyether polyol, and a polyisocyanate can be used.

[0086] Examples of the polyester polyol include polyester polyols obtained by reacting a low molecular weight polyol with a polycarboxylic acid, polyester polyols obtained by ring-opening polymerization of a cyclic ester compound such as ε-caprolactone, and polyester polyols obtained by copolymerizing these. These polyester polyols can be used alone or in combination of two or more kinds.

[0087] Examples of low molecular weight polyols include aliphatic polyols having a molecular weight of about 50 to 300, such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, and 1,3-butanediol; polyols having an aliphatic cyclic structure, such as cyclohexanedimethanol; and polyols having an aromatic structure, such as bisphenol A and bisphenol F. Examples of polycarboxylic acids that can be used in the production of polyester polyols include aliphatic polycarboxylic acids, such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic polycarboxylic acids, such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; and anhydrides or esters thereof. In addition, polyester polyurethane polyols having urethane bonds in the molecular structure, which are obtained by modifying the above polyester polyols with polyisocyanates, can also be used as polyester polyols. These polyester polyols can be used alone or in combination of two or more.

[0088] The polyether polyol may be, for example, a product obtained by addition polymerization of an alkylene oxide using one or more compounds having two or more active hydrogen atoms as an initiator. Examples of the compound having two or more active hydrogen atoms include propylene glycol, trimethylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, glycerin, diglycerin, trimethylolethane, trimethylolpropane, water, hexanetriol, and the like. Examples of the alkylene oxide include propylene oxide, butylene oxide, styrene oxide, epichlorohydrin, tetrahydrofuran, and the like. In addition, as the polyether polyol, a polyether polyurethane polyol having a urethane bond in the molecular structure obtained by modifying the above polyether polyol with a polyisocyanate may be used. These polyether polyols may be used alone or in combination of two or more.

[0089] Examples of the polyisocyanate include polyisocyanates having an aliphatic cyclic structure such as cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, and isophorone diisocyanate; aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, crude diphenylmethane diisocyanate, phenylene diisocyanate, tolylene diisocyanate, and naphthalene diisocyanate; and aliphatic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate. Among these, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, and crude diphenylmethane diisocyanate are preferred. These polyisocyanates can be used alone or in combination of two or more kinds.

[0090] As the silane coupling agent, a conventionally known silane coupling agent can be used, and for example, the same silane coupling agent as that used in the above-mentioned gas barrier resin composition is preferably used. By including a silane coupling agent in the primer layer, the interlayer adhesion with the barrier coat layer can be improved.

[0091] As the silica fine particles, conventionally known silica can be used. In particular, when the urethane resin is polyether polyurethane, the primer layer contains silica fine particles, which can suppress blocking during winding in the production process of the gas barrier vapor deposition film.

[0092] <Third embodiment> 1(C) is an example in which a substrate 1, a coating layer 3, and an aluminum-deposited film 2 are laminated in this order. This embodiment differs from the second embodiment in that the aluminum-deposited film 2 is located on the surface of the barrier film. The explanation of the substrate 1, the aluminum-deposited film 2, and the coating layer 3 is omitted because they are the same as those in the first embodiment.

[0093] As shown in the second and third embodiments, in the present invention, the coating layer 3 may be disposed between the substrate 1 and the aluminum vapor-deposited film 2, or on the aluminum vapor-deposited film, i.e., on the outermost surface of the barrier film.

[0094] <Pinhole occurrence rate> The barrier film of the present invention is characterized in that the pinhole occurrence rate due to the aluminum vapor deposition film 3 is 0.100% or less. Regarding the deterioration of the barrier property of a barrier film containing an aluminum vapor deposition film, in a conventional vapor deposition apparatus, due to the structure of the vapor deposition apparatus in which vapor deposition is performed roll-to-roll, the vapor-deposited barrier film passes through multiple rolls such as guide rolls while being wound into a roll. The present inventors have found that when the aluminum vapor deposition surface directly touches the roll surface, pinholes are generated and the barrier property is deteriorated. This deterioration of the barrier property due to the direct contact between the aluminum vapor deposition film and the roll occurs even when the aluminum vapor deposition film has a certain thickness or more, and the deterioration of the barrier property cannot be avoided with the configuration of a normal vapor deposition apparatus. For this reason, the barrier film of the present invention adopts a configuration in which the vapor deposition apparatus is changed so that the aluminum vapor deposition film does not come into direct contact with the roll. That is, the surfaces of the barrier film that come into contact with the guide rolls or the like are all on the non-aluminum vapor deposition film side, i.e., the substrate side side, thereby significantly reducing the number of pinholes generated in the aluminum vapor deposition film, i.e., the pinhole occurrence rate, and thus successfully suppressing the deterioration of the barrier property.

[0095] The pinhole incidence rate is determined by the following procedure, the details of which are described in the Examples. First, a sample is taken from an arbitrary location of a barrier film having an aluminum vapor deposition film. Next, the sample is set on the stage of an optical microscope, and a halogen light source with an illuminance of 5500±550 lux is irradiated from below onto one side of the barrier film.

[0096] Thereafter, a 2.8 mm×2.1 mm area is magnified from the other surface side of the barrier film using an optical microscope, and a 1280×964 pixel image is obtained from the magnified image.

[0097] Next, the acquired image is converted into a 256-level monochrome image using image analysis software, and a brightness histogram is created for the monochrome image, with the horizontal axis representing 256 levels of brightness and the vertical axis representing the number of pixels, from which the most frequent brightness value is determined.

[0098] 2 is an example of a luminance histogram of Example 2 described later, in which the most frequent luminance (Mode in the figure) is 14. Similarly, FIG. 4 is an example of a luminance histogram of Comparative Example 1 described later, in which the most frequent luminance (Mode in the figure) is 16.

[0099] The gradation value obtained by adding 30 gradations to the most frequent luminance value is set as the threshold value, and the luminance is binarized by setting values ​​below this threshold as black pixels and values ​​above this threshold as white pixels. The pinhole occurrence rate (%) is calculated using the following formula. Pinhole occurrence rate (%) = 100 x (white pixels / total pixels)

[0100] Fig. 3 is an example of binarizing the luminance histogram of Fig. 2. Similarly, Fig. 5 is an example of binarizing the luminance histogram of Fig. 4.

[0101] The pinhole occurrence rate (%) in this embodiment is the average value obtained by sampling n=5.

[0102] The pinhole incidence is 0.100% or less, preferably 0.050% or less, and particularly preferably 0.030% or less. By making the pinhole incidence 0.100% or less, it is possible to suppress the occurrence of pinholes and suppress the deterioration of barrier properties. The lower limit of the pinhole incidence is preferably 0.010% or more, more preferably 0.003% or more, and even more preferably 0.001% or more.

[0103] The barrier film according to the present embodiment preferably has an oxygen permeability of 0.30 cc / m at 23° C. and 90% RH according to JIS K 7126-2. 2 ·day·atm or less, preferably 0.20cc / m 2 ·day·atm or less. The lower limit is preferably 0.01 cc / m 2 ·day·atm or more, preferably 0.10cc / m 2 ·day·atm or higher.

[0104] The barrier film according to the present embodiment preferably has a water vapor transmission rate of 0.30 g / m at 40° C. and 100% RH as measured in accordance with JIS K 7129 B method. 2 ·day or less, preferably 0.20g / m 2 ·day or less. The lower limit is preferably 0.01 g / m 2 ·day or more, preferably 0.05g / m 2 ·day or more, particularly preferably 0.10 g / m 2 ·day or more.

[0105] As described above, according to the present invention, by suppressing pinholes originating from the aluminum vapor deposition film, it is possible to obtain a barrier film having high gas barrier properties, and a laminate using the same.

[0106] (Laminate) An example of a laminate formed by using the barrier film according to the present embodiment will be described. The laminate may include the barrier film of the present invention and a sealant layer. Specifically, the laminate may include a sealant layer on the outermost surface of the barrier film shown in FIG. 1 opposite to the substrate, via an adhesive layer. Also, the laminate may include a second substrate made of polyamide or the like, a second adhesive layer, and a sealant layer, in this order, on the outermost surface of the barrier film shown in FIG. 1 opposite to the substrate. The laminate of the present invention is a barrier film having at least one heat-sealable layer laminated thereon, in which a heat-sealable thermoplastic resin is laminated as the innermost layer by melt extrusion coating with or without an adhesive layer, and is provided with sealability such as heat sealing. Specific laminate configurations include biaxially oriented polyester film / adhesive layer / barrier film / adhesive layer / sealant layer. A printed layer may be formed on either surface of the barrier film. By providing a printed layer, it is possible to display the contents.

[0107] Examples of the thermoplastic resin constituting the sealant layer include films containing one or more of resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, polymethylpentene, polystyrene, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-propylene copolymer, elastomer, etc. The thickness of the sealant layer 7 is preferably 3 to 100 μm, more preferably 15 to 70 μm.

[0108] (packaged products) The laminate described above can be used as a packaging product such as a packaging bag for containing contents such as food by forming the laminate into a bag shape with the sealant layer on the inside. EXAMPLES

[0109] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these descriptions in any way.

[0110] Example 1 A biaxially oriented polyethylene terephthalate film having a thickness of 12 μm (total light transmittance of 88.6% measured according to JIS K 7361-1:1997) was used as the substrate 1, and an aluminum vapor deposition film 2 was formed on one surface of the substrate 1 to produce a barrier film having the layer structure shown in FIG. 1(A).

[0111] The aluminum vapor deposition film 2 was formed by attaching the PET film to the delivery roll of a vacuum vapor deposition device and evaporating metallic aluminum using a conventionally known resistance heating method under the following vapor deposition conditions: Note that the process from vapor deposition to roll winding was carried out in the vacuum vapor deposition device without the aluminum vapor deposition surface coming into contact with any of the guide rolls. Deposition speed: 400m / sec Vacuum degree: 2.0×10 -1 Pa Deposition thickness: 37 nm Optical density (OD value): 2.20

[0112] Example 2 The barrier film of Example 2 was produced under the same conditions as in Example 1, except that the deposition speed was changed to 200 m / sec, the deposition thickness was changed to 75 nm, and the optical density (OD value) was changed to 4.40.

[0113] Comparative Example 1 The barrier film of Comparative Example 1 was produced under the same conditions as in Example 1, except that the optical density (OD value) was set to 3.50, and the process from deposition to roll winding was carried out in a vacuum deposition apparatus with the aluminum-deposited surface in contact with a guide roll.

[0114] Comparative Example 2 The barrier film of Comparative Example 2 was produced under the same conditions as those of Comparative Example 1, except that the optical density (OD value) was set to 3.64.

[0115] Comparative Example 3 The barrier film of Comparative Example 3 was produced under the same conditions as those of Comparative Example 1, except that the optical density (OD value) was set to 3.71.

[0116] Comparative Example 4 A commercially available aluminum-deposited PET film (PET 12 μm, optical density (OD value) 2.70) was used as the barrier film of Comparative Example 4.

[0117] <Measurement of pinhole occurrence rate> For the barrier films of Examples 1 to 3 and Comparative Examples 1 to 4, the pinhole occurrence rate was measured using the following device and in the following manner. Observation device: Carl Zeiss AxioImager M1m Image acquisition software: Axio Vision 4.6

[0118] First, a sample was taken from an arbitrary location of a barrier film having an aluminum vapor deposition film.

[0119] Next, the sample was set on the stage of an optical microscope with the PET film side facing down, and one side of the barrier film was irradiated from below with halogen light from a halogen light source at an illuminance of 5500±550 lux. The illuminance measurement conditions were as follows: <Light intensity adjustment conditions> Light source: Halogen lamp Light source intensity scale: 4 Lighting angle of incidence: 90 degrees (transmitted light) Field of view: Max. Aperture (aperture stop): 0.8 Illumination on stage: 5500±550 lux (lx) Illuminance meter: Konica Minolta T-10A, JIS C 1609-1:2006 general AA class illuminance meter, DIN 5032 Part7 1985 Class B compliant

[0120] Thereafter, a 2.8 mm x 2.1 mm area was magnified from the other side of the barrier film using an optical microscope, and the magnified image was captured as a 1280 x 964 pixel image under the following conditions. <Image acquisition conditions> ·CCD: Axio Cam MRc5 Photodetector: 2 / 3” CCD -Photosensitive pixels: 5 million pixels Sensor size per pixel: 6.8μm×6.8μm ·Exposure time 20ms - Maximum brightness adjustment 100% ·BF (bright field) Objective lens: x5 Eyepiece: x10x <Image adjustment conditions> Brightness adjustment: -0.5 Contrast: 1.00 Gamma adjustment: 0.6 -Image resolution for analysis: 1280 x 964 = 1.23 million pixels

[0121] Next, the acquired image was converted into a monochrome image with 256 gradations using image analysis software, and a luminance histogram was created with the horizontal axis being 256 gradations of luminance and the vertical axis being the number of pixels in the monochrome image, from which the most frequent luminance was calculated. The gradation value obtained by adding 30 gradations to the most frequent luminance was set as a threshold, and luminance was binarized with pixels below the threshold being black pixels and pixels above the threshold (from "mode + 30 gradations" to 255 gradations) being white pixels (equivalent to pinholes), and the pinhole occurrence rate (%) was calculated using the following formula. The results are shown in Table 1. Pinhole occurrence rate (%) = 100 x (white pixels / total pixels)

[0122] The following was used for the binarization process. Software used: ImageJ Binarization algorithm: Otsu method

[0123] The pinhole occurrence rate (%) in this embodiment was determined as an average value obtained by sampling n=5.

[0124] <Barrier property measurement> For the barrier films of Examples 1 to 3 and Comparative Examples 1 to 4, the water vapor permeability and oxygen permeability were measured.

[0125] The water vapor transmission rate was measured in accordance with JIS K 7129 B method using a water vapor transmission rate measuring device (manufactured by Mocon, product name "PERMATORAN-W 3 / 31") at 40°C and 100% RH. The oxygen transmission rate was measured in accordance with JIS K 7126-2 using an oxygen transmission rate measuring device (manufactured by Mocon, product name "OX-TRAN 2 / 20") at 23°C and 90% RH. The results are shown in Table 1. Here, +30 in the table means a gradation obtained by adding 30 gradations to the most frequent luminance value. Note that +50 in the table is a reference value in the case where the gradation obtained by adding 50 gradations to the most frequent luminance value is used as the threshold value.

[0126] [Table 1]

[0127] It can be seen from Table 1 that the barrier film according to this embodiment, which has a pinhole incidence rate of 0.100% or less, has excellent oxygen barrier properties and water vapor barrier properties. [Explanation of symbols]

[0128] 1 Base material 2. Aluminum deposition film 3 Covering layer

Claims

1. A barrier film comprising a resin substrate and an aluminum vapor deposition film laminated in this order, The barrier film has a pinhole incidence rate, as defined below, of 0.100% or less. <Definition of Pinhole Occurrence Rate> One side of the barrier film is irradiated with a halogen light source at an illuminance of 5500±550 lux, and an arbitrary 2.8 mm × 2.1 mm area is enlarged from the other side of the barrier film using an optical microscope, and a 1280 × 964 pixel image of the enlarged image is obtained. Using image analysis software, the captured image is converted into a monochrome image with 256 gradations. The value obtained by adding 30 gradations to the most frequent luminance value in the monochrome image is set as a threshold, and the luminance is binarized by setting values ​​below the threshold as black pixels and values ​​above the threshold as white pixels, and is calculated using the following formula. Pinhole occurrence rate (%) = 100 x (white pixels / total pixels)

2. 2. The barrier film according to claim 1, further comprising a coating layer disposed between the resin substrate and the aluminum vapor-deposited film or on the aluminum vapor-deposited film.

3. 3. The barrier film according to claim 1, wherein the coating layer is a cured product of a resin composition containing an alkoxysilane and a hydroxyl group-containing water-soluble resin.

4. The barrier film according to claim 1 or 2 has an oxygen permeability of 0.3 cc / m at 23° C. and 90% RH as measured in accordance with JIS K 7126-2. 2 A barrier film having a resistance of 0.1 to 1000 MPa (day-atm or less).

5. The barrier film according to claim 1 or 2 has a water vapor transmission rate of 0.3 g / m at 40° C. and 100% RH as measured according to JIS K 7129 B method. 2 - A barrier film having a shelf life of less than 10 days.

6. A laminate comprising the barrier film according to claim 1 or 2 and a sealant layer.

7. A packaging product comprising the laminate of claim 6.

Citation Information

Patent Citations

  • Gas-barrier aluminum vapor deposition film and laminated film using same

    WO2018147137A1